2017
DOI: 10.7150/jca.19273
|View full text |Cite
|
Sign up to set email alerts
|

FH535 Inhibits Proliferation and Motility of Colon Cancer Cells by Targeting Wnt/β-catenin Signaling Pathway

Abstract: Aberrant Wnt/β-catenin pathway activation is frequently observed in human colorectal cancer (CRC) and has become a promising target for CRC treatment. Our study aimed to evaluate the effect of FH535, a small molecule inhibitor of Wnt/β-catenin pathway, on two colon cancer cell lines, HT29 and SW480. We found FH535 significantly inhibited colon cancer cell proliferation in vitro and induced cell cycle arrest. Moreover, FH535 inhibited colon cancer xenograft growth in vivo. Wound-healing assay and Transwell assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…A possible explanation for the enhanced sensitization of colon cancer cells to the effects of known chemotherapeutic agents, by SYNAP may be related to the ability of SYNAP to reduce the levels of survivin, a key protein in carcinogenesis almost uniformly overexpressed in these tumours (Hernandez et al, ). In fact, survivin overexpression has been associated with cancer progression, chemoresistance and angiogenesis, with apoptosis inhibition and shortened survival in cancer patients (Ling et al, ; Hernandez et al, ; Souza et al, ; Singh et al, ; Chen et al, ). In addition, inhibition of survivin improved the uptake of drugs by cancer cells with a notable enhancement of their anticancer activity (Singh et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the enhanced sensitization of colon cancer cells to the effects of known chemotherapeutic agents, by SYNAP may be related to the ability of SYNAP to reduce the levels of survivin, a key protein in carcinogenesis almost uniformly overexpressed in these tumours (Hernandez et al, ). In fact, survivin overexpression has been associated with cancer progression, chemoresistance and angiogenesis, with apoptosis inhibition and shortened survival in cancer patients (Ling et al, ; Hernandez et al, ; Souza et al, ; Singh et al, ; Chen et al, ). In addition, inhibition of survivin improved the uptake of drugs by cancer cells with a notable enhancement of their anticancer activity (Singh et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…FH535 is an inhibitor of Wnt/β-catenin signaling and dual antagonist of PPARγ/δ activity. It suppresses β-catenin/Tcf-mediated transcription and inhibits β-catenin and GRIP1 recruitment to PPARγ and δ (26,27).…”
Section: Methodsmentioning
confidence: 99%
“…FH535 is considered as twofold small molecule inhibitor of β-catenin/TCF/LEF and peroxisome proliferator-activated receptors (PPARs) [ 17 ]. Earlier studies revealed that FH535 hampers the growth of colon, lung, breast, hepatocellular cancer cells [ 18 ], and suppresses angiogenesis and pancreatic cancer xenograft growth [ 19 ].…”
Section: Introductionmentioning
confidence: 99%